2016
DOI: 10.2147/ijn.s99731
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic analysis of Zein nanoparticles/PLGA triblock in situ forming implants for glimepiride

Abstract: Objectives The study aims at applying pharmaceutical nanotechnology and D-optimal fractional factorial design to screen and optimize the high-risk variables affecting the performance of a complex drug delivery system consisting of glimepiride–Zein nanoparticles and inclusion of the optimized formula with thermoresponsive triblock copolymers in in situ gel. Methods Sixteen nanoparticle formulations were prepared by liquid–liquid phase separation method according to the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The major obstacle in the design of ISG formulations is the high initial burst of the drug after administration 6 , 13 16 . Accordingly, the goal was to sustain the release of GMD from the ISG formulation by controlling its initial burst from the designed formula.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The major obstacle in the design of ISG formulations is the high initial burst of the drug after administration 6 , 13 16 . Accordingly, the goal was to sustain the release of GMD from the ISG formulation by controlling its initial burst from the designed formula.…”
Section: Resultsmentioning
confidence: 99%
“…At the same concentrations of both X 2 and X 3 , as the concentration of PLGA increased from 20 to 30%, Y 3 decreased from 2972.38 in F6 to 2517.45 µg in F7, from 2928.37 in F12 to 2181.8 µg in F10, and from 3039.05 in F11 to 2570.78 µg in F4. This observation can be attributed to the presence of PLGA at higher concentrations, which hastens the solidification of the formulation and subsequently reduces the leaching of GMD to the surrounding phase 6 , 15 , 17 , 18 . To a certain extent, the same finding was attained in the initial burst after 2 h in the previous formulations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported 3.3 % and 17.3 % drug release after 2 and 24 h, respectively. This ISG system exhibited pseudoplastic behaviour with a reduction of glimepiride release rate as the concentration of the polymer was increased [57].…”
Section: Isg Systems Based On Drug Nanocrystals and Nanoparticlesmentioning
confidence: 99%